Minding their Place : Space and Religious Hierarchy in Ibn al-Qayyim's Aḥkām ahl al-dhimma - Bosanquet, Antonia, (The History of Christian-Muslim Relations ;, 2021)
Antonia Bosanquet's Minding Their Place is the first full-length study of Ibn al-Qayyim's (d. 751/1350) collection of rulings relating to non-Muslim subjects, Aḥkām ahl al-dhimma . It offers a detailed study of the structure, content and authorial method of the work, arguing that it represents the author's personal composition rather than a synthesis of medieval rulings, as it has often been understood. On this basis, Antonia Bosanquet analyses how Ibn al-Qayyim's presentation of rulings in Aḥkām ahl al-dhimma uses space to convey his view of religious hierarchy. She considers his answer to the question of whether non-Muslims have a place in the Abode of Islam, how this is defined and how his definition contributes to Ibn al-Qayyim's broader theological world-view.